Peran perpustakaan sebagai media komunikasi ilmiah - khairina khairina (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
Scientists from several centuries ago has conducted formally scholarly communication activities for the deployment of science and research that has been done. Media used at that time still in the form of leaflets research results in scientific articles or through a book. Until the time of publication of a magazine, researchers have seriously publish their writings in the media, because in addition to more regular publication, will also be faster than the process of publishing a book. Along with the development of knowledge and technology, the use of print media for the dissemination of knowledge has gradually been replaced on the electronic media. The library, which in this case has evolved into a knowledge management institutions have an important role in the dissemination of knowledge with its media and its function as a means of scientific communication. In this paper will be presented on the role and efforts in building a library of scientific communication media. Among them is the management of electronic journals that will bring changes to the communications media. The result is the need for further study of the media that was built by the library to the ongoing scholary communication. Because the library is an institution that is supposed or provide a platform to support the development of science. Keywords: Scholarly Communication, Electronic Journals, Publication, Knowledge Management